Human Neutrophil Alloantigen Genotype Frequencies Among Syrian Population - Hauck-Dlimi, Barbara; Damrah, Mohammed; Achenbach, Susanne; Ott, Stephan; Zimmermann, Robert; Zingsem, Jürgen; Strobel, Julian (Clinical Laboratory, 2018)
BACKGROUND: Human neutrophil antigens (HNA) are able to provoke allo- and autoimmune antibodies which lead to reactions like autoimmune and neonatal neutropenia. However, until now no data about HNA genotype distribution in Syrian population exists. The aim of this study was to determine the HNA allele frequencies in the largest group asking for asylum in Germany since 2015. Allele frequencies were compared to data from German blood donors. Therefore, we calculated the risk of alloimmunization and associated transfusion reactions, as well as the risk of developing neonatal neutropenia for newborns of mixed race couples. METHODS: We isolated DNA from blood samples of 100 Syrian volunteers and typed them for HNA-1, -3, -4, and -5 by using a commercial polymerase chain reaction kit with sequence-specific primers (SSP-PCR). Then, we compared the HNA genotype distribution with data from Germans and different populations from literature. RESULTS: In Syrian population the gene frequencies for HNA-1a, HNA-1b, and HNA-1c were 0.375, 0.580, and 0.040, for HNA-3a and -3b 0.742 and 0.258, for HNA-4a and -4b 0.860 and 0.140, and for HNA-5a and -5bw 0.660 and 0.340, respectively. No statistically significant differences between Syrian and German gene frequencies were found. CONCLUSIONS: This study is the first to report HNA gene frequencies in Syrian population. There is no significant difference of HNA genotype frequencies compared to the German population. Therefore, no elevated alloimmunization risks in transfusion of blood and blood components and in pregnancy of mixed race couples exist.
EVALuna2:36010